2019
DOI: 10.24996/ijs.2019.60.11.8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation the Cytomegalovirus (CMV) IgM Antibodies and Viral DNA Presence with Rheumatoid Arthritis (RA) in Iraqi Patients

Abstract: In the Iraqi population, a high incidence (82.7%) of rheumatoid arthritis (RA) has been reported among the suspected patient. Many investigators studied the microbial infectious present in Iraqi patients with RA; however, to the best of our knowledge, there is no previous study detected the CMV DNA and antibodies to RA disease. Hence, the current study aimed to investigate the presence of CMV DNA and antibodies in Iraqi RA patients. A total of 58 blood samples were collected from patients with clinical signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Another explanation for this failure is that the intensity of the infection with the coronavirus might vary depending on a number of parameters, including age, chronic conditions, and co-morbidities with COVID-19. This reinforces the likelihood of varying results depending on other circumstances [31].The high value of INR indicates the presence of coagulopathy is highly significantly with severe disease and increased mortality in patients with COVID-19 [32]. It has been suggested that elevation of INR can be used as rapid and inexpensive diagnosis for COVID-19 infection [15].…”
Section: Discussionmentioning
confidence: 94%
“…Another explanation for this failure is that the intensity of the infection with the coronavirus might vary depending on a number of parameters, including age, chronic conditions, and co-morbidities with COVID-19. This reinforces the likelihood of varying results depending on other circumstances [31].The high value of INR indicates the presence of coagulopathy is highly significantly with severe disease and increased mortality in patients with COVID-19 [32]. It has been suggested that elevation of INR can be used as rapid and inexpensive diagnosis for COVID-19 infection [15].…”
Section: Discussionmentioning
confidence: 94%